2020
DOI: 10.3390/f11010090
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome DNA Methylation Associated With Differentially Expressed Genes Regulated Anthocyanin Biosynthesis Within Flower Color Chimera of Ornamental Tree Prunus mume

Abstract: DNA methylation is one of the best-studied epigenetic modifications involved in many biological processes. However, little is known about the epigenetic mechanism for flower color chimera of Prunus mume (Japanese apricot, mei). Using bisulfate sequencing and RNA sequencing, we analyzed the white (FBW) and red (FBR) petals collected from an individual tree of Japanese apricot cv. ‘Fuban Tiaozhi’ mei to reveal the different changes in methylation patterns associated with gene expression leading to significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 86 publications
1
11
0
Order By: Relevance
“…However, when limiting the analysis to certain genes, the relationship between ML and gene expression did not always follow this rule. Similar result can be found in the result of previous research ( Ma et al, 2018 ; Jiang et al, 2020 ). A more likely explanation was the complexity of the process of floral scent biosynthesis, so that methylation is not the only regulation factor.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, when limiting the analysis to certain genes, the relationship between ML and gene expression did not always follow this rule. Similar result can be found in the result of previous research ( Ma et al, 2018 ; Jiang et al, 2020 ). A more likely explanation was the complexity of the process of floral scent biosynthesis, so that methylation is not the only regulation factor.…”
Section: Discussionsupporting
confidence: 92%
“…The results are consistent with findings from the petals of P. mume cv. ‘FT’ ( Jiang et al, 2020 ), apples, and Arabidopsis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is one of the most common epigenetic modifications in eukaryotes and is believed to play a vital role in various biological processes, including transcription regulation, embryogenesis, cellular differentiation, genomic imprinting, X-chromosome inactivation, transposon silencing and so on [ 25 31 ]. In plants and some vertebrates, DNA methylation is also involved in the regulation of colouration, such as flower colours [ 32 ], eggshell colours [ 33 ] and animal skin and coat colours [ 34 ]; this suggests that it is also likely involved in the regulation of shell colour. However, to date, no published studies have addressed this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding these changes requires rigorous analysis at the genome-wide level and recent studies have indicated the role of the methylated region in positively or negatively regulating the gene expression in specific tissue types [25,26]. Previous studies indicate the role of deposition of backfat is one such aspect associated with growth rate, meat quality, and reproductive performance [27].…”
Section: Introductionmentioning
confidence: 99%